1998
DOI: 10.1017/s0317167100033813
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Entrapment of the Lateral Cutaneous Nerve of the Calf Presenting as a Peroneal Sensory Neuropathy

Abstract: ABSTRACT:Objective:Presentation of an unusual case of congenital entrapment of the lateral cutaneous nerve of the calf (LCNC) mimicking a peroneal sensory neuropathy.Methods:We report the case of a 16-year-old girl with a 3 year history of progressive tingling, numbness and pain in her right calf precipitated by athletic activities involving repeated flexion and extension of the knee. A Tinel's sign was present over the common peroneal nerve in the distal popliteal fossa but absent at the fibular neck. Motor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…In a case study performed by Hackam and Zwimpfer [7], the patient showed symptoms of tingling, numbness, and pain in the right calf. The Tinel sign was positive at the distal popliteal fossa.…”
Section: Discussionmentioning
confidence: 99%
“…In a case study performed by Hackam and Zwimpfer [7], the patient showed symptoms of tingling, numbness, and pain in the right calf. The Tinel sign was positive at the distal popliteal fossa.…”
Section: Discussionmentioning
confidence: 99%
“…The third and fourth cases4 5 are due to a structural lesion, but only the third case5 (due to a congenital anomaly of the biceps femoris tendon) was treated/cured by surgery. The tendon was transected and repaired with Z-plasty and on follow-up all symptoms disappeared completely.…”
Section: Discussionmentioning
confidence: 99%
“…3 Congenital entrapment of the LCNC has also been reported recently. 5 In all of these cases, dysesthesias and numbness occurred on the lateral surface of the knee, spreading approximately two-thirds of the way down the posterolateral calf.…”
mentioning
confidence: 94%